2014
DOI: 10.1038/ncomms4813
|View full text |Cite
|
Sign up to set email alerts
|

Generalized self-assembly of scalable two-dimensional transition metal oxide nanosheets

Abstract: Two-dimensional (2D) transition metal oxide systems present exotic electronic properties and high specific surface areas, and also demonstrate promising applications ranging from electronics to energy storage. Yet, in contrast to other types of nanostructures, the question as to whether we could assemble 2D nanomaterials with an atomic thickness from molecules in a general way, which may give them some interesting properties such as those of graphene, still remains unresolved. Herein, we report a generalized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
624
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 819 publications
(655 citation statements)
references
References 49 publications
12
624
0
7
Order By: Relevance
“…[45], the 2D ZnO structures can be obtained using conductive glass substrates, such as indium-doped ZnO and indium tin oxide (ITO). This was supported by several published works [27,39,42].…”
Section: Electrodepositionssupporting
confidence: 71%
See 4 more Smart Citations
“…[45], the 2D ZnO structures can be obtained using conductive glass substrates, such as indium-doped ZnO and indium tin oxide (ITO). This was supported by several published works [27,39,42].…”
Section: Electrodepositionssupporting
confidence: 71%
“…The XRD patterns reveal the polycrystalline nature and can be indexed as hexagonal wurtzite structures of ZnO. Several published research studies showed the preferred orientation along the c-axis orientation of the (0001) plane [9,27,36,39,42,55]. No significant difference in the XRD pattern was noticed for different morphologies of the prepared 2D ZnO.…”
Section: The Crystal Structural and The Morphology Of The 2d Znomentioning
confidence: 87%
See 3 more Smart Citations